Regenerated cement stabilized macadam mixture and preparation method thereof

By chemically strengthening recycled coarse aggregate, introducing basalt fiber and industrial solid waste, etc., recycled cement-stabilized gravel mixture is prepared, which solves the problem of single performance of recycled aggregate and achieves performance improvement and environmental benefits.

CN120794503APending Publication Date: 2025-10-17THE 2ND ENG CO LTD OF CHINA RAILWAY URBAN CONSTR GRP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511104493.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

The existing means of strengthening recycled aggregates are relatively simple, making it difficult to fully optimize their performance, resulting in difficulty in meeting engineering requirements in road construction.

Method used

By comprehensively utilizing chemically strengthened recycled coarse aggregate, introducing basalt fiber, replacing fine aggregate with industrial solid waste, adding waste rubber powder and other means, a recycled cement-stabilized gravel mixture is prepared to improve its performance.

Benefits of technology

The comprehensive performance of recycled aggregates has been improved, the compressive strength and resistance to shrinkage deformation have been increased, road cracks have been reduced, maintenance costs have been reduced, and resource recycling and environmental protection have been promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of pavement materials, in particular to a regenerated cement stabilized macadam mixture and a preparation method thereof. The mixture is prepared from chemical enhanced recycled coarse aggregate, basalt fiber and other raw materials, and the chemical enhanced recycled coarse aggregate is prepared through the steps of hydrochloric acid solution treatment, chemical modification solution soaking and the like. The preparation method comprises the following steps: weighing the raw materials according to the ratio, mechanically stirring part of the raw materials uniformly, adding the polycarboxylate superplasticizer, stirring, adding water, and stirring. The mixture has remarkable advantages, realizes efficient recycling and reusing of waste resources, improves the resource utilization rate, improves the pavement performance, reduces the maintenance cost, reduces ecological damage and environmental pollution, meets the environmental protection requirements, reduces the raw material and road maintenance and repair cost, has good economic benefits, and provides an effective scheme for sustainable development of related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pavement materials, and in particular to a recycled cement-stabilized crushed stone mixture and a preparation method thereof. Background Art

[0002] With society's increasing demands for sustainable development and environmental protection, the materials used in road construction and maintenance are facing significant challenges. Traditional natural aggregates like crushed stone and sandstone are becoming increasingly scarce, with rising mining costs and increasing environmental damage. Therefore, the search for sustainable, environmentally friendly, and high-performance alternative materials has become a key research topic in road construction and maintenance.

[0003] Recycled aggregate, as a recyclable pavement material, has garnered extensive attention and research in recent years. However, its current application in road construction still faces several challenges. First, the performance of recycled aggregate is unstable, and key indicators such as strength and durability often fail to meet engineering requirements. Second, existing methods for strengthening recycled aggregate are relatively limited, often only improving specific performance aspects and failing to achieve comprehensive optimization.

[0004] Therefore, to address the above-mentioned issues, the present invention proposes a recycled cement-stabilized gravel mixture and a method for preparing the same. By comprehensively utilizing chemically reinforced recycled aggregate, introducing basalt fiber to enhance road performance, replacing fine aggregate with industrial solid waste to leverage the volcanic ash activity and micro-aggregate filling effect, and adding waste rubber powder to improve crack resistance, the goal is to comprehensively enhance the performance of the recycled cement-stabilized gravel mixture, providing a higher-quality, environmentally friendly, and economical material option for road construction and maintenance. The implementation of this invention is expected to promote the widespread use of recycled aggregate in road construction, fostering resource recycling and sustainable development. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to propose a recycled cement-stabilized crushed stone mixture and a preparation method thereof, so as to solve the problem that the existing recycled aggregate strengthening methods are relatively single and can often only improve the performance of a certain aspect but cannot achieve comprehensive optimization.

[0006] Based on the above objectives, the present invention provides a recycled cement-stabilized gravel mixture, which is prepared from the following raw materials, by weight: 50-80 parts of chemically strengthened recycled coarse aggregate, 0.05-0.1 parts of basalt fiber, 40-80 parts of alkali-activated lithium slag, 3-7 parts of cement, 5-15 parts of steel slag powder, 5-20 parts of mineral powder, 1-3 parts of waste rubber powder, 0.5-2 parts of polycarboxylic acid water reducer and 6-10 parts of water.

[0007] Further, the preparation method of the chemically reinforced recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1 mol / L-0.2 mol / L hydrochloric acid solution for 24-48 h, then the recycled aggregate is washed with clean water, and then placed in a chemical modification liquid for 8-15 h, with a bath ratio of 1:15-20, and after taking out, the recycled aggregate is dried by using an oven to obtain the chemically reinforced recycled coarse aggregate.

[0008] Further, the recycled coarse aggregate is obtained by crushing and screening waste concrete, and is divided into three grades according to particle size, i.e., 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm, and the aggregate gradation corresponds to 35-55, 60-80 and 100, respectively.

[0009] Further, the preparation steps of the chemical modification liquid are as follows: S1: under a nitrogen atmosphere, pentavinylhexylamine, methyl acrylate and dimethylaminoethyl acrylate quaternary ammonium salt are added to anhydrous methanol, stirred at 0-5℃ for 1.5-2.5 h, then warmed to 60℃ and stirred for 0.8-1.2 h to remove the methanol solvent, then warmed to 100℃ and stirred for 2 h, and then warmed to 140℃ and stirred for 2 h, and then cooled to obtain an amino-terminated branched polymer; S2: the amino-terminated branched polymer is mixed with water to obtain a chemical modification liquid.

[0010] Preferably, the weight ratio of pentavinylhexylamine, methyl acrylate and dimethylaminoethyl acrylate quaternary ammonium salt in step S1 is 12.5:4.3:1-4.

[0011] Preferably, the weight ratio of the amino-terminated branched polymer and water in step S2 is 1:80-120.

[0012] Preferably, the average length of the basalt fiber is 9 mm-50 mm.

[0013] Preferably, the alkali-activated lithium slag is obtained by activating the activity of the lithium slag with 4%-6% water glass (modulus 1-3) of the mass of the lithium slag. Preferably, the lithium slag is a salt method lithium slag produced by lithium mica-salt pressure boiling method, with a specific surface area of 300 m 2 ·kg -1 -500 m 2 ·kg -1 , and a density of 2 g·cm -3 -3 g·cm -3The loss on ignition is 3-7%, and the mass percentage composition of the main components is: SiO2 45-60%, Al2O3 20-30%, CaO 6-8%, SO3 6-8%, K2O 0.1-0.3%, Na2O 0.1-0.3%, MgO 0.1-0.5%, and Fe2O3 1-2%.

[0014] Preferably, the cement is any one of P·O 42.5, P·F 32.5, P·F 42.5, P·C 32.5, and P·C 42.5.

[0015] Preferably, the steel slag micro-powder has a specific surface area of 400-600 m 2 ·kg -1 The loss on ignition is 3-7%, and the mass percentage composition of the main components is: SiO2 45-60%, Al2O3 20-30%, CaO 6-8%, SO3 6-8%, K2O 0.1-0.3%, Na2O 0.1-0.3%, MgO 0.1-0.5%, and Fe2O3 1-2%.

[0016] Preferably, the mineral powder is S95 blast furnace slag powder.

[0017] Preferably, the waste rubber powder has a mesh size of 40-80 mesh.

[0018] Further, the application also provides a preparation method of the recycled cement stabilized gravel mixture, comprising the following steps: (1) according to the proportioning, the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag micro-powder, mineral powder, waste rubber powder, polycarboxylic acid water reducing agent and water are weighed; (2) the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag micro-powder, mineral powder and waste rubber powder are mechanically stirred uniformly, then the polycarboxylic acid water reducing agent is added, stirred for 30-40 s, finally the water is added into the mixture and mechanically stirred uniformly, to obtain the recycled cement stabilized gravel mixture.

[0019] The application has the following beneficial effects: The recycled cement stabilized gravel mixture has significant beneficial effects, and meets the current concept of sustainable development and green pavement.

[0020] In terms of resource utilization, the application realizes efficient recycling and reuse of waste resources. By crushing and screening the waste concrete to obtain recycled coarse aggregate, the dependence on natural aggregate is reduced, and the problem of the increasingly scarce natural aggregate resources is alleviated. Meanwhile, the reasonable utilization of industrial waste such as lithium slag and steel slag micro-powder further improves the utilization rate of resources, reduces the pressure of waste on the environment, and promotes the recycling of resources.

[0021] In terms of performance improvement, the mixture has excellent compressive strength and anti-shrinkage deformation capacity. Through the preparation of chemically strengthened recycled coarse aggregate, the impurities and loose layer on the surface of the aggregate are removed, and a stable film structure is formed on the surface, enhancing the interfacial bonding between the aggregate and other materials, improving the internal structure of the mixture, and enabling it to withstand greater pressure. At the same time, the comprehensive effect of multiple strengthening methods effectively reduces the dry shrinkage coefficient of the mixture, reduces the occurrence of road cracks, improves the flatness and service life of the road, and reduces the maintenance cost of the road.

[0022] In terms of environmental benefits, the present application reduces the damage to the ecological environment during the mining of natural aggregate and reduces the pollution of industrial waste to soil, water and air. In addition, the preparation process of the mixture uses conventional instruments and reagents, which meets the environmental protection requirements and reduces the negative impact on the environment.

[0023] In terms of economic cost, the use of recycled coarse aggregate and industrial waste to replace part of the natural material reduces the cost of raw materials. At the same time, due to the improvement of the performance of the mixture, the maintenance and repair cost of the road is reduced, which has significant economic benefits.

[0024] In summary, the recycled cement stabilized gravel mixture of the present application has significant advantages in resource utilization, performance improvement, environmental benefits and economic cost, and provides an effective solution for the sustainable development of road engineering and pavement field. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present application more clear and explicit, the present application is further described in detail below in combination with specific examples.

[0026] In the following examples and comparative examples, the instruments and equipment involved are conventional instruments and equipment unless otherwise specified; the reagents and raw materials involved are commercially available conventional reagents unless otherwise specified; the experimental methods involved are conventional methods unless otherwise specified; The recycled coarse aggregate is obtained by crushing and screening waste concrete, and the crushed aggregate is distributed into three grades of 4.75-9.5mm, 9.5-19mm and 19-31.5mm according to particle size, and the aggregate gradation is 35, 60 and 100 respectively.

[0027] The specific surface area of lithium slag is 421.24m 2 ·kg -1 , and the density is 2.56g·cm -3, the loss on ignition is 5.21%, and the mass percentage composition of main components is: SiO2 51.22%, Al2O3 24.31%, CaO 7.15%, SO3 7.41%, K2O 0.24%, Na2O 0.21%, MgO 0.32%, Fe2O3 2.22%; The steel slag micro-powder has a specific surface area of 515.36m 2 ·kg -1 The mass percentage composition of main components is: SiO2 15.24%, CaO 36.32%, MgO 7.56%, Fe2O3 7.58%, Al2O3 8.56%.

[0028] Example 1: A recycled cement stabilized macadam mixture, the components and weight parts are as follows: chemical strengthening recycled coarse aggregate 60 parts, basalt fiber 0.08 parts (average length 25 mm), alkali-activated lithium slag 50 parts, cement 4 parts (type P·O42.5), steel slag micro-powder 5 parts, mineral powder 5 parts (S95 blast furnace slag powder), waste rubber powder 1 part (mesh number 60 mesh), polycarboxylic acid water reducer 1 part (type PCE-202), and water 8 parts; The preparation method of the chemical strengthening recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1 mol / L hydrochloric acid solution for 24 h, then the recycled aggregate is washed with clean water, and then placed in a chemical modification liquid for 12 h, the bath ratio is 1:15, after taking out, the recycled aggregate is dried by using an oven, to obtain the chemical strengthening recycled coarse aggregate; The preparation method of the chemical modification liquid is as follows: S1: under nitrogen atmosphere, 12.5g penta-vinyl hexylamine, 4.3g methyl acrylate, 1g dimethylaminoethyl acrylate quaternary ammonium salt are added into 100g anhydrous methanol, stirred at 0℃ for 1.5h, then warmed to 60℃ and stirred for 1h to remove methanol solvent, then warmed to 100℃ and stirred for 2h, 140℃ and stirred for 2h, and then cooled to obtain an amino-terminated branched polymer; S2: the amino-terminated branched polymer and water are mixed in a weight ratio of 1:100 to obtain a chemical modification liquid; The alkali-activated lithium slag is obtained by activating the activity of lithium slag with a water glass (modulus 2.6) of 5% lithium slag mass; The preparation method of the recycled cement stabilized macadam mixture is as follows: (1) the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag micro-powder, mineral powder, waste rubber powder, polycarboxylic acid water reducer and water are weighed according to the proportion; (2) The chemical reinforced recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder and waste rubber powder are mechanically stirred uniformly, then the polycarboxylic acid water reducing agent is added, stirred for 35s, and finally the water is added into the mixture and mechanically stirred uniformly to obtain the recycled cement stabilized gravel mixture.

[0029] Example 2 A recycled cement stabilized gravel mixture, the components and weight parts are as follows: chemical reinforced recycled coarse aggregate 80 parts, basalt fiber 0.08 parts (average length 25mm), alkali-activated lithium slag 60 parts, cement 4 parts (type P·O42.5), steel slag powder 5 parts, mineral powder 5 parts (S95 blast furnace slag powder), waste rubber powder 1.5 parts (mesh 60), polycarboxylic acid water reducing agent 1 part (type PCE-202) and water 8.5 parts; The preparation method of the chemical reinforced recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1mol / L hydrochloric acid solution for 24h, then the recycled aggregate is washed with clean water, and then placed in a chemical modification liquid for 12h, the bath ratio is 1:15, after taking out, the recycled aggregate is dried by using an oven to obtain the chemical reinforced recycled coarse aggregate; The preparation method of the chemical modification liquid is as follows: S1: Under the nitrogen atmosphere, 12.5g of penta-vinyl hexylamine, 4.3g of methyl acrylate and 2g of dimethylaminoethyl acrylate quaternary ammonium salt are added into 100g of anhydrous methanol, stirred at 0℃ for 2h, then warmed to 60℃ and stirred for 1h to remove the methanol solvent, then warmed to 100℃ and stirred for 2h, 140℃ and stirred for 2h, and then cooled to obtain an amino-terminated branched polymer; S2: The amino-terminated branched polymer and water are mixed in a weight ratio of 1:100 to obtain a chemical modification liquid; The alkali-activated lithium slag is obtained by activating the activity of lithium slag with a water glass (modulus 2.6) of 5% lithium slag mass; The preparation method of the recycled cement stabilized gravel mixture is as follows: (1) The chemical reinforced recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, waste rubber powder, polycarboxylic acid water reducing agent and water are weighed according to the proportion; (2) The chemical reinforced recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder and waste rubber powder are mechanically stirred uniformly, then the polycarboxylic acid water reducing agent is added, stirred for 35s, and finally the water is added into the mixture and mechanically stirred uniformly to obtain the recycled cement stabilized gravel mixture.

[0030] Example 3 A recycled cement stabilized macadam mixture, each component and weight fraction are as follows: chemical strengthening recycled coarse aggregate 60 parts, basalt fiber 0.08 parts (average length 25 mm), alkali-activated lithium slag 50 parts, cement 5 parts (type P·O42.5), steel slag powder 5 parts, mineral powder 5 parts (S95 blast furnace slag powder), waste rubber powder 1.5 parts (mesh 60), polycarboxylic acid water reducer 1 part (type PCE-202), and water 8.5 parts; The preparation method of the chemical strengthening recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1 mol / L hydrochloric acid solution for 24 h, then the recycled aggregate is washed with clean water, and then placed in a chemical modification liquid for 12 h, with a bath ratio of 1:18, and after taking out, the recycled aggregate is dried by using an oven to obtain the chemical strengthening recycled coarse aggregate; The preparation method of the chemical modification liquid is as follows: S1: under a nitrogen atmosphere, 12.5 g of penta-vinyl hexylamine, 4.3 g of methyl acrylate, and 3 g of dimethylaminoethyl acrylate quaternary ammonium salt are added to 100 g of anhydrous methanol, stirred at 0℃ for 3 h, then warmed to 60℃ and stirred for 1 h to remove the methanol solvent, then warmed to 100℃ and stirred for 2 h, 140℃ and stirred for 2 h, and then cooled to obtain an amino-terminated branched polymer; S2: the amino-terminated branched polymer and water are mixed in a weight ratio of 1:100 to obtain a chemical modification liquid; The alkali-activated lithium slag is obtained by activating the activity of lithium slag with a water glass (modulus 2.6) of 5% lithium slag mass; The preparation method of the recycled cement stabilized macadam mixture is as follows: (1) chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, waste rubber powder, polycarboxylic acid water reducer, and water are weighed according to the proportion; (2) the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, and waste rubber powder are mechanically stirred uniformly, then the polycarboxylic acid water reducer is added, stirred for 35 s, and finally the water is added to the mixture and mechanically stirred uniformly to obtain the recycled cement stabilized macadam mixture.

[0031] Example 4: A recycled cement stabilized macadam mixture, each component and weight fraction are as follows: chemical strengthening recycled coarse aggregate 80 parts, basalt fiber 0.08 parts (average length 25 mm), alkali-activated lithium slag 60 parts, cement 5 parts (type P·O42.5), steel slag powder 5 parts, mineral powder 5 parts (S95 blast furnace slag powder), waste rubber powder 1.5 parts (mesh 60), polycarboxylic acid water reducer 1 part (type PCE-202), and water 9 parts; The preparation method of the chemical strengthening recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1 mol / L hydrochloric acid solution for 24 h, then the recycled aggregate is washed with clean water, and then placed in a chemical modification liquid for 12 h, with a bath ratio of 1:20, and after being taken out, the recycled aggregate is dried by using an oven to obtain the chemical strengthening recycled coarse aggregate; The preparation method of the chemical modification liquid is as follows: S1: under a nitrogen atmosphere, 12.5 g of penta-vinyl hexylamine, 4.3 g of methyl acrylate, and 4 g of dimethylaminoethyl acrylate quaternary ammonium salt are added to 100 g of anhydrous methanol, stirred at 0℃ for 1.5 h, then warmed to 60℃ and stirred for 1 h to remove the methanol solvent, then warmed to 100℃ and stirred for 2 h, and then warmed to 140℃ and stirred for 2 h, and then cooled to obtain an amino-terminated branched polymer; S2: the amino-terminated branched polymer and water are mixed in a weight ratio of 1:100 to obtain a chemical modification liquid; The alkali-activated lithium slag is obtained by activating the activity of the lithium slag with a water glass (modulus 2.6) of 5% of the mass of the lithium slag; The preparation method of the recycled cement stabilized gravel mixture is as follows: (1) the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, waste rubber powder, polycarboxylic acid water reducer, and water are weighed according to the proportion; (2) the chemical strengthening recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, and waste rubber powder are mechanically stirred uniformly, then the polycarboxylic acid water reducer is added, stirred for 35 s, and finally the water is added to the mixture and mechanically stirred uniformly to obtain the recycled cement stabilized gravel mixture.

[0032] Comparative Example 1: The difference between this comparative example and Example 2 is that the recycled coarse aggregate is used instead of the chemical strengthening recycled coarse aggregate; Comparative Example 2: The difference between this comparative example and Example 2 is that no dimethylaminoethyl acrylate quaternary ammonium salt is added in the preparation step of the chemical modification liquid.

[0033] Comparative Example 3: The difference between this comparative example and Example 2 is that the amino-terminated branched polymer in the preparation step of the chemical modification liquid is replaced by penta-vinyl hexylamine; Comparative Example 4: A mixture, the components and weight parts are as follows: recycled coarse aggregate 80 parts, amino-terminated branched polymer 12 parts, basalt fiber 0.08 parts (average length 25 mm), alkali-activated lithium slag 60 parts, cement 5 parts (type P·O42.5), steel slag powder 5 parts, mineral powder 5 parts (S95 blast furnace slag powder), waste rubber powder 1.5 parts (mesh 60), polycarboxylic acid water reducer 1 part (type PCE-202) and water 9 parts; The remaining steps are the same as those in Example 2; Performance test: standard test pieces were prepared according to the Highway Engineering Inorganic Binder Stabilized Material Test Specification (JTG E51-2009), and the unconfined compressive strength and dry shrinkage coefficient of the test pieces of Examples 1-4 and Comparative Examples 1-4 were measured, and the results are shown in Table 1.

[0034] Table 1 Performance test results

[0035] Data analysis: From the data of Examples 1-4 in Table 1, it can be seen that the representative value of the 7-day unconfined compressive strength of the cement stabilized material for heavy traffic, heavy / medium traffic and light traffic highway asphalt pavement base in the Highway Asphalt Pavement Design Specification (JTG D50-2006) is 3.5-4.5MPa, 3-4MPa, 2.5-3.5MPa, respectively, and it can be seen that the strength of the examples meets the specification requirements, and also has good anti-dry shrinkage deformation ability.

[0036] From the data of Example 2 and Comparative Example 1 in Table 1, it can be seen that Example 2 is significantly better than Comparative Example 1 in unconfined compressive strength, and has a smaller dry shrinkage coefficient. Comparative Example 1 uses recycled coarse aggregate to replace chemically strengthened recycled coarse aggregate, which may be the key to the performance difference. The presence of a large number of microcracks and attached old mortar on the surface of the recycled coarse aggregate makes it less cohesive with other components, and the structure is loose, thereby affecting the overall compressive strength and dry shrinkage resistance of the mixture. The chemically strengthened recycled coarse aggregate is treated with hydrochloric acid and a chemical modification liquid, on the one hand, the hydrochloric acid can remove part of the impurities and loose layer on the surface of the recycled coarse aggregate, on the other hand, the chemical modification liquid may form a stable film structure on the surface of the aggregate, enhancing the interfacial adhesion between the aggregate and other materials, improving the internal structure of the mixture, so that it can withstand greater pressure, while reducing dry shrinkage, thereby improving the compressive strength and dry shrinkage resistance.

[0037] As can be seen from the data of Example 2 and Comparative Example 2 in Table 1, the unconfined compressive strength of Example 2 is higher than that of Comparative Example 2, and the drying shrinkage coefficient is lower. The difference in the preparation of the chemical modifying liquid, i.e., the absence of dimethylaminoethyl acrylate quaternary ammonium salt in Comparative Example 2, can have a significant impact on the performance of the mixture. The dimethylaminoethyl acrylate quaternary ammonium salt can have special chemical properties that contribute to the formation of a specific structure of the polymer during the reaction with penta-vinyl hexylamine and methyl acrylate to form the amino-terminated branched polymer. This structure can enable the chemical modifying liquid to better interact with the surface of the recycled coarse aggregate during the treatment, enhancing the modification effect on the aggregate. In contrast, the absence of this component in Comparative Example 2 limits the modification effect of the chemical modifying liquid on the aggregate, resulting in insufficient bonding between the aggregate and other components, and insufficient stability of the internal structure of the mixture, which leads to a decrease in compressive strength and an increase in drying shrinkage coefficient.

[0038] As can be seen from the data of Example 2 and Comparative Example 3 in Table 1, Example 2 is superior to Comparative Example 3 in terms of unconfined compressive strength and anti-drying shrinkage performance. The replacement of the amino-terminated branched polymer in the preparation of the chemical modifying liquid with penta-vinyl hexylamine in Comparative Example 3 can change the mechanism of action of the chemical modifying liquid on the recycled coarse aggregate. The amino-terminated branched polymer has a unique branched structure and functional group distribution that enables it to better interact with the surface of the recycled coarse aggregate, forming a stable bonding layer. The structure of penta-vinyl hexylamine is relatively simple and may not be able to effectively improve the surface properties of the aggregate as effectively as the amino-terminated branched polymer, resulting in weaker bonding between the aggregate and other materials and a less dense overall structure of the mixture. Therefore, Comparative Example 3 has lower compressive strength and greater drying shrinkage deformation, while Example 2 exhibits better performance.

[0039] As can be seen from the data of Example 2 and Comparative Example 4 in Table 1, Example 2 is superior to Comparative Example 4 in terms of unconfined compressive strength and anti-drying shrinkage performance. The direct addition of the amino-terminated branched polymer as a component to the mixture in Comparative Example 4, rather than using it to prepare a chemical modifying liquid to treat the recycled coarse aggregate, can result in different modes of action of the amino-terminated branched polymer in the mixture. In Example 2, the amino-terminated branched polymer in the chemical modifying liquid can fully contact and interact with the surface of the recycled coarse aggregate, improving the surface properties of the aggregate and enhancing its bonding with other components. In Comparative Example 4, the directly added amino-terminated branched polymer may not be uniformly dispersed and fully bonded with the surface of the aggregate, and cannot effectively improve the interfacial properties between the aggregate and other materials, resulting in defects in the internal structure of the mixture and poor structural stability, which in turn leads to lower compressive strength and anti-drying shrinkage performance compared to Example 2.

[0040] Those skilled in the art should understand that the above discussion of any embodiment is only intended to be exemplary in nature and is not intended to suggest that the present application is limited to these examples; under the concept of the present application, the above embodiments or technical features among different embodiments can be combined, steps can be implemented in any order, and there are many other variations of different aspects of the present application as described above, which are not provided in details for the sake of brevity.

Claims

1. A recycled cement-stabilized gravel mixture, characterized in that: The invention is prepared from the following raw materials in parts by weight: 50-80 parts of chemically strengthened recycled coarse aggregate, 0.05-0.1 parts of basalt fiber, 40-80 parts of alkali-activated lithium slag, 3-7 parts of cement, 5-15 parts of steel slag powder, 5-20 parts of mineral powder, 1-3 parts of waste rubber powder, 0.5-2 parts of polycarboxylic acid water reducer and 6-10 parts of water; The preparation method of the chemically strengthened recycled coarse aggregate is as follows: first, the recycled coarse aggregate is placed in a 0.1mol / L-0.2mol / L hydrochloric acid solution for 24-48 hours, then rinsed, and then placed in a chemical modification solution for 8-15 hours, with a bath ratio of 1:15-20, taken out and dried to obtain the chemically strengthened recycled coarse aggregate; The preparation steps of the chemical modification liquid are as follows: S1: Under a nitrogen atmosphere, pentavinylhexylamine, methyl acrylate, and dimethylaminoethyl acrylate quaternary ammonium salt were added to anhydrous methanol, and the mixture was stirred at 0-5°C for 1.5-2.5 hours. The mixture was then heated to 60°C and stirred for 0.8-1.2 hours to remove the methanol solvent. The mixture was then heated to 100°C and stirred for 2 hours, and then stirred at 140°C for 2 hours. The mixture was then cooled to obtain an amino-terminated branched polymer. S2: mixing the amino-terminated branched polymer and water to obtain a chemically modified solution; In step S1, the weight ratio of pentavinylhexylamine, methyl acrylate and dimethylaminoethyl acrylate quaternary ammonium salt is 12.5:4.3:1-4; and in step S2, the weight ratio of amino-terminated branched polymer and water is 1:80-120.

2. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The recycled coarse aggregate is obtained by crushing and screening waste concrete, and is divided into three grades according to particle size: 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm, and the aggregate gradations correspond to 35-55, 60-80 and 100 respectively.

3. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The average length of the basalt fiber is 9 mm to 50 mm.

4. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The alkali-activated lithium slag is obtained by activating the activity of the lithium slag with water glass having a modulus of 1-3 and a content of 4%-6% of the lithium slag mass.

5. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The steel slag powder has a specific surface area of ​​400-600m 2 kg -1 of ground steel slag powder.

6. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The cement is any one of P·O42.5, P·F 32.5, P·F 42.5, P·C 32.5, and P·C 42.

5.

7. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The mineral powder is S95 blast furnace slag powder.

8. The recycled cement-stabilized crushed stone mixture according to claim 1, characterized in that: The mesh size of the waste rubber powder is 40-80 meshes.

9. A recycled cement-stabilized crushed stone mixture according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh chemically reinforced recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder, waste rubber powder, polycarboxylate water reducer and water according to the proportion; (2) The chemically reinforced recycled coarse aggregate, basalt fiber, alkali-activated lithium slag, cement, steel slag powder, mineral powder and waste rubber powder are mechanically mixed evenly, and then polycarboxylic acid water reducer is added and stirred for 30-40 seconds. Finally, water is added to the mixture and mechanically stirred evenly to obtain a recycled cement-stabilized gravel mixture.

Citation Information

Cited By

  • Preparation method of alkali activator activated fiber reinforced steel slag concrete

    CN121672980A